Capital Market Financing, Firm Growth, and Firm Size Distribution - Didier, Tatiana; Levine, Ross; Schmukler, Sergio L. (World Bank, Washington, DC, 2015)
How many and which firms issue equity and bonds in domestic and international markets, how do these firms grow relative to non-issuing firms, and how does firm performance vary along the firm size distribution? To evaluate these questions, a new data set is constructed by matching data on firm-level capital raising activity with balance sheet data for 45,527 listed firms in 51 countries. Three main patterns emerge from the analysis. (1) Only a few large firms issue equity or bonds, and among them a small subset has raised a large proportion of the funds raised during the 1990s and 2000s. (2) Issuers grow faster than non-issuers in assets, sales, and employment, that is, firms do not simply use securities markets to adjust their financial accounts. (3) The firm size distribution of issuers evolves differently from that of non-issuers, tightening among issuers and widening among non-issuers.